CORE Learning Model for Enhancing Mathematical HOTS, Motivation, and Students’ Self-Efficacy Development - Nanik Tri Purwaningsih; Aldo Setiawan; Deny Hadi Siswanto (Jurnal Pendidikan dan Inovasi Pembelajaran, 2026)
This study aims to analyze the implementation of the CORE (Connecting, Organizing, Reflecting, Extending) learning model in mathematics instruction at SMP N 1 Galur. This research employed a qualitative descriptive approach with data collected through observations, semi-structured interviews, and documentation analysis. The findings reveal that the Connecting stage helps students understand abstract mathematical concepts by relating them to contextual problems, while the Organizing stage encourages collaboration and intellectual responsibility through group activities. The Reflecting and Extending stages strengthen conceptual understanding through metacognitive reflection and HOTS-based problem-solving activities. The implementation of the CORE model improves students’ learning motivation, reduces mathematical anxiety, and enhances self-efficacy. However, limited instructional time remains a major challenge in its implementation. This study concludes that the CORE model effectively creates an active, collaborative, and student-centered mathematics learning environment that supports deeper conceptual mastery.